2022
DOI: 10.1186/s12974-022-02472-4
|View full text |Cite
|
Sign up to set email alerts
|

A crosstalk between gut and brain in sepsis-induced cognitive decline

Abstract: Background Sepsis is a potentially fatal disease characterized by acute organ failure that affects more than 30 million people worldwide. Inflammation is strongly associated with sepsis, and patients can experience impairments in memory, concentration, verbal fluency, and executive functioning after being discharged from the hospital. We hypothesize that sepsis disrupts the microbiota–gut–brain axis homeostasis triggering cognitive impairment. This immune activation persists during treatment, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…While no human studies are available, a recent preclinical study has shown how the GM plays a part in sepsis-associated encephalopathy by improving neurological outcomes when indole-3-propionic acid, a microbial neuroprotective metabolite, is produced, leading to the inhibition of NLRP3 inflammasome activation and IL-1β secretion in the microglia [ 26 ]. Similar preclinical results have been found in model of sepsis-induced cognitive decline [ 25 ], emphasizing the link between GM dysbiosis and the brain.…”
Section: The Gut Microbiota and The Hostsupporting
confidence: 84%
See 2 more Smart Citations
“…While no human studies are available, a recent preclinical study has shown how the GM plays a part in sepsis-associated encephalopathy by improving neurological outcomes when indole-3-propionic acid, a microbial neuroprotective metabolite, is produced, leading to the inhibition of NLRP3 inflammasome activation and IL-1β secretion in the microglia [ 26 ]. Similar preclinical results have been found in model of sepsis-induced cognitive decline [ 25 ], emphasizing the link between GM dysbiosis and the brain.…”
Section: The Gut Microbiota and The Hostsupporting
confidence: 84%
“…These molecules affect memory, learning, behavior, and locomotion. Unbalanced molecular communication contributes to neurodegenerative and neuropsychiatric diseases [ 23 ], traumatic brain injury (TBI) [ 24 ], and sepsis-correlated brain impairment [ 25 , 26 ]. The gut–brain axis (GBA) bidirectionally connects the central nervous system with the enteric one.…”
Section: The Gut Microbiota and The Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus is well known for its role in long-term memory and MWM-associated spatial learning and memory in rodents has been linked to the hippocampus ( Liu et al, 2021 ). As CLP surgery has been shown to cause sustained cognitive impairment 5–15 days post-surgery and a previous study performed the MWM test at 1–2 weeks post CLP surgery to assess cognitive function in SAE rats ( Shen et al, 2020 ; Giridharan et al, 2022 ), we further analyzed the ALFF values and metabolism changes during the same time period. In our results, the increased ALFF values in the hippocampus supported the deteriorated behavioral results in the MWM test, which was consistent with a previous studies using the MWM test to evaluate hippocampal function ( Barnhart et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh fecal samples ( n = 8/group) were collected into individual sterile EP tubes on two consecutive mornings ( Wang et al, 2019 ) after the MWM test and immediately frozen at −80°C until analysis ( Giridharan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%